2021
DOI: 10.1111/btp.13046
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling drivers of thermal physiology: Community‐wide cold shock recovery of butterflies under natural conditions

Abstract: Physiological strategies of terrestrial ectotherms are a delicate interplay between species’ traits and their physical environment. Several theories and overarching hypotheses seek to explain strategies related to thermal physiology with respect to organisms and their environments. However, most of these have been investigated under controlled laboratory conditions with lab‐reared or otherwise acclimated individuals, removing the effect of environmental acclimation. This study examines an in‐situ physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
2
0
0
Order By: Relevance
“…Darker butterflies had stronger thermal buffering abilities than paler butterflies, and darker butterfly species also could tolerate higher temperatures than paler butterflies. This is in‐line with previous evidence that dark butterflies heat up and cool down faster than pale butterflies at a given level of solar radiation (Watt, 1968 ), and achieve higher body temperatures than pale individuals (Dufour et al, 2018 ; Khazan et al, 2022 ). This is also in line with comparative studies across temperate latitudes (Zeuss et al, 2014 ), which found a higher incidence of darker species in cooler conditions, possibly also related to the advantage of darker species in being able to warm themselves in cooler conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Darker butterflies had stronger thermal buffering abilities than paler butterflies, and darker butterfly species also could tolerate higher temperatures than paler butterflies. This is in‐line with previous evidence that dark butterflies heat up and cool down faster than pale butterflies at a given level of solar radiation (Watt, 1968 ), and achieve higher body temperatures than pale individuals (Dufour et al, 2018 ; Khazan et al, 2022 ). This is also in line with comparative studies across temperate latitudes (Zeuss et al, 2014 ), which found a higher incidence of darker species in cooler conditions, possibly also related to the advantage of darker species in being able to warm themselves in cooler conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Darker butterflies had stronger thermal buffering abilities and could tolerate higher temperatures than paler species. This is in-line with previous evidence that dark butterflies heat up and cool down faster than pale butterflies at a given level of solar radiation (Watt 1968), and achieve higher body temperatures than pale individuals (Dufour et al 2018;Khazan et al 2022). This is also in line with comparative temperate studies across latitudes (Zeuss et al 2014), which found a higher incidence of darker species in cooler conditions, possibly also related to the advantage of dark species in being able to warm in cooler conditions.…”
Section: Wing Coloursupporting
confidence: 91%